2005
DOI: 10.1095/biolreprod.105.043182
|View full text |Cite
|
Sign up to set email alerts
|

Role of FOXO1A in the Regulation of Insulin-Like Growth Factor-Binding Protein-1 in Human Endometrial Cells: Interaction with Progesterone Receptor1

Abstract: Insulin-like growth factor-binding protein-1 (IGFBP1) is a major secretory product of the decidualized endometrium. In the present study, we investigated the role of two transcription factors, progesterone receptor (PGR) and a member of the forkhead box class O family of transcription factors (FOXO1A), in the regulation of the IGFBP1 gene in endometrial cells. Human endometrial fibroblasts (HuF) expressed FOXO1A, progesterone receptor A (PGRA), and progesterone receptor B (PGRB) proteins, whereas the endometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…Interaction of nuclear hormone receptors with members of the FOXO protein family downstream of PI3-kinase/ AKT has also been reported. The progesterone receptor, which shares a consensus DNA binding sequence with the GR, has been reported to cooperate with FOXO1 and bind adjacent on the promoter of the insulin-like growth factor-binding protein-1 (IGFBP1) [46,47]. Additionally, binding sites for both GR and FOXO1 exist in the glucocorticoid response element of the glucose-6-phosphate transporter gene promoter where both proteins cooperate to activate its transcription [48].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of nuclear hormone receptors with members of the FOXO protein family downstream of PI3-kinase/ AKT has also been reported. The progesterone receptor, which shares a consensus DNA binding sequence with the GR, has been reported to cooperate with FOXO1 and bind adjacent on the promoter of the insulin-like growth factor-binding protein-1 (IGFBP1) [46,47]. Additionally, binding sites for both GR and FOXO1 exist in the glucocorticoid response element of the glucose-6-phosphate transporter gene promoter where both proteins cooperate to activate its transcription [48].…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 is needed for survival of EPC populations in culture, and thus modulation by IGFBPs, including IGFBP3, is certainly plausible (34). Previously, we showed that quiescent human retinal endothelial cells (representing the resident endothelial cells of the retina) express high levels of IGFBP3 (35).…”
Section: Igfbp3-expressing Hscs Inhibit Neovascularization By Protectmentioning
confidence: 97%
“…They are known to be involved in the regulation of IGFBP-1 expression during decidualization (5,(19)(20)(21).…”
Section: Recruitment Of Transcription Factors To the Igfbp-1 Enhancermentioning
confidence: 99%